2020
DOI: 10.1097/iop.0000000000001614
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion in Upper Eyelid Flaps: Effects of Rotation and Stretching Measured With Laser Speckle Contrast Imaging in Patients

Abstract: Purpose: The aim of this study was to investigate how the blood perfusion in human upper eyelid skin flaps is affected by the length of the flap and the degree of stretching and rotation of the flap. Methods: Twenty-nine upper eyelids were dissected as part of a blepharoplastic procedure in patients. The 1-cm wide proximal end of the flap remains attached, to mimic a random pattern skin flap (hereafter called a “skin flap”). Blood perfusion was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 9 publications
6
16
1
Order By: Relevance
“…However, the combination of rotation and stretching led to a significant reduction in perfusion. 18 This is in line with the results of our previous study on porcine eyelid flaps. 24 It, therefore, appears to be necessary to achieve a compromise between the length of the flap and the degree to which it must be rotated and stretched to cover a defect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the combination of rotation and stretching led to a significant reduction in perfusion. 18 This is in line with the results of our previous study on porcine eyelid flaps. 24 It, therefore, appears to be necessary to achieve a compromise between the length of the flap and the degree to which it must be rotated and stretched to cover a defect.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with a previous study by our group, in which it was shown that the perfusion in a human cutaneous upper eyelid flap was mainly preserved in the first 15 mm from the flap base, but very low beyond this. 12 , 18 Furthermore, 6 weeks was required for the distal tip of the glabellar flap, beyond 20 mm, to be reperfused. Reperfusion of the flap tip thus follows the same pattern as the revascularization of a free skin graft, and presumably depends on angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with a previous study by our group, in which it was shown that the perfusion in a human cutaneous upper eyelid flap was primarily maintained in the first 15 mm from the flap base but very limited beyond this distance. 5,8 Rotating and stretching the flap was found to reduce blood perfusion. 8 Administering diathermy to the base of the flap has also been shown to significantly reduced blood perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…5,8 Rotating and stretching the flap was found to reduce blood perfusion. 8 Administering diathermy to the base of the flap has also been shown to significantly reduced blood perfusion. 5 Since the distal part of the flap does not seem to be perfused, a free full-thickness skin graft could be considered as well.…”
Section: Discussionmentioning
confidence: 99%
“…In a random pattern skin flap, the blood supply is derived from many small unspecified vessels (i.e., diffuse perfusion in the microvascular network, without blood supply from a larger blood vessel). Recent studies indicate that the dissection of a random advancement flap will result in hypoperfusion and that oxygenation depends on different factors, such as the length and thickness of the flap, 39 whether it consists of skin only or skin and orbicularis muscle, 119 whether it is stretched or rotated, 68 and whether its base is subjected to diathermy. 120 A more detailed description of how the perfusion is affected is given below.…”
Section: Perfusion and Oxygenation Monitoring In Oculoplastic Surgerymentioning
confidence: 99%